PEMBENTUKAN SIKAP SOSIAL MELALUI PEMBELAJARAN IPS PADA SISWA KELAS VII SMP NEGERI 3 PALANGKA RAYA - Desiana Natalia (JURNAL SOCIUS, 2016)
Social attitudes is awareness within the individual. In SMP Negeri 3 Palangkaraya VII class, the teacher was instrumental in the formation of social attitudes of students, especially through social studies learning. The purpose of this researc his to know how Social Attitude Formation Through Social Learning In Seventh Grade Students of SMP Negeri 3 Palangkaraya. This study used a qualitative method. Results of the study is that the SMP Negeri 3 Palangkaraya implement Curriculum 2013, in which there are aspects of attitude assessment. Social attitudes of students can be formed in a social studies lesson with the teacher giving an example of a good attitude to the students both in the classroom and outside the classroom. Keywords: Social Attitudes and Social Learning Sikap sosial adalah kesadaran dalam diri individu. Di SMP Negeri 3 kelas Palangkaraya VII, guru berperan dalam pembentukan sikap sosial siswa, terutama melalui studi sosial pembelajaran. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana Sikap Formasi Sosial Melalui Pembelajaran Sosial Dalam Siswa Kelas VII SMP Negeri 3 Palangkaraya. Penelitian ini menggunakan metode kualitatif. Hasil dari studi ini adalah bahwa SMP Negeri 3 Palangkaraya menerapkan Kurikulum 2013, di mana ada aspek penilaian sikap. sikap sosial siswa dapat dibentuk dalam pelajaran IPS dengan guru memberikan contoh sikap yang baik kepada siswa baik di kelas maupun di luar kelas.Kata kunci: Sikap Sosial dan Pembelajaran Sosial